Nicotinic Acetylcholine Receptor Ligands, Cognitive Function, and Preclinical Approaches to Drug Discovery. Issue 3 (23rd August 2018) - Terry, Alvin V; Callahan, Patrick M
Abstract: : Interest in nicotinic acetylcholine receptor (nAChR) ligands as potential therapeutic agents for cognitive disorders began more than 30 years ago when it was first demonstrated that the tobacco alkaloid nicotine could improve cognitive function in nicotine-deprived smokers as well as nonsmokers. Numerous animal and human studies now indicate that nicotine and a variety of nAChR ligands have the potential to improve multiple domains of cognition including attention, spatial learning, working memory, recognition memory, and executive function. The purpose of this review is to (1) discuss several pharmacologic strategies that have been developed to enhance nAChR activity (eg, agonist, partial agonist, and positive allosteric modulator) and improve cognitive function, (2) provide a brief overview of some of the more common rodent behavioral tasks with established translational validity that have been used to evaluate nAChR ligands for effects on cognitive function, and (3) briefly discuss some of the topics of debate regarding the development of optimal therapeutic strategies using nAChR ligands. Because of their densities in the mammalian brain and the amount of literature available, the review primarily focuses on ligands of the high-affinity α4β2* nAChR ("*" indicates the possible presence of additional subunits in the complex) and the low-affinity α7 nAChR. The behavioral task discussion focuses on representative methods that have been designed to model specific domains of cognition that are relevant to human neuropsychiatric disorders and often evaluated in human clinical trials. Implications: The preclinical literature continues to grow in support of the development of nAChR ligands for a variety of illnesses that affect humans. However, to date, no new nAChR ligand has been approved for any condition other than nicotine dependence. As discussed in this review, the studies conducted to date provide the impetus for continuing efforts to develop new nAChR strategies (ie, beyond simple agonist and partial agonist approaches) as well as to refine current behavioral strategies and create new animal models to address translational gaps in the drug discovery process.